Dakwah Ethic In Pluralistic Society - karni, awis (Universitas Islam Negeri Imam Bonjol Padang, 2005)
Dakwah ethic presents in Al-Qur'an as Messenger of Allah done. His attitudes and activities in dakwah include his dakwah activity inpluralistic society. Pluralism does not mean that all religion arenght, but it means that all religion have the right to exist with the risk under its followers This article discourse part of Al-Quran that gives argument in order to do dakwah activities in pluralistic society